(untitled) (CAHIERS MAGELLANES-NS, 2025)
Background: Topical corticosteroids (TCs) are widely used dermatological medications that can lead to significant side effects, particularly when used without medical supervision. In Saudi Arabia, a previous study reported that 43.1% of users did so without prescriptions, with female gender identified as a risk factor. Objective: This study aimed to evaluate the prevalence of topical corticosteroid usage without prescriptions among females in the Kingdom of Saudi Arabia (KSA). Methods: A cross-sectional survey was conducted from July to November 2024, employing a structured questionnaire administered to female citizens aged 15-40 who used TCs without prescriptions. Participants were recruited from diverse provinces in KSA, and data on demographics, usage patterns, awareness of side effects, and sources of information regarding TCs were collected. Results: A total of 400 females participated, with a mean age of 30.4 years. The findings revealed a high prevalence of TCs usage without prescriptions, with 72.3% purchasing them independently. Alarmingly, 90% believed their products contained TCs. Notably, 44.8% used TCs for skin whitening, and 27.8% for acne treatment. Most participants (57.8%) sourced information from non-professional avenues, primarily the internet. Awareness of side effects was high, with over half acknowledging potential risks, yet a significant proportion (39%) remained unaware of any side effects. Statistical analysis indicated significant correlations between prescription use and demographic factors such as age, marital status, education, and occupation. Conclusion: This study highlights alarming rates of topical corticosteroid use without prescriptions among females in KSA, predominantly for cosmetic purposes. The reliance on non-professional sources for information poses serious public health risks, underscoring an urgent need for targeted educational interventions to enhance awareness of the potential dangers associated with unsupervised TCs use. Future strategies should focus on improving medical oversight and educating the public about safe practices in dermatological care.